Clinical review of 23 patients with tuberculous peritonitis: Presenting features and diagnosis - Poyrazoglu, Orhan K.; Timurkaan, Mustafa; Yalniz, Mehmet; Ataseven, Huseyin; Dogukan, Muruvvet; Bahcecioglu, Ibrahim H. (Wiley, 2008)
OBJECTIVE: To better identify which clinical, laboratory, radiological and invasive procedures were most useful in diagnosing tuberculous peritonitis and to assess the methods in order to reach the diagnosis in future cases. METHODS: Tuberculous peritonitis cases diagnosed between 2000 and 2006 were reviewed retrospectively. Their clinical presentation, physical examination, laboratory and diagnostic methods were evaluated. RESULTS: Twenty-three cases of tuberculous peritonitis were diagnosed. The mean age of the patients were 30 +/- 11 years and 16 were women. The mean duration of symptoms prior to diagnosis was 3.6 months. All patients presented with abdominal pain. Abdominal swelling (91.3%), loss of appetite (87%) and weight loss (82.6%) were the other commonest symptoms. The major physical findings were ascites (78.3%) and fever (60.9%). The serum ascites albumin gradient was < 1.1 g/dL in all. An ascites fast bacilli smear was positive in 12 (52.2%) patients. Skin tests with purified protein derivative, adenosine deaminase and polymerase chain reaction were performed in seven, four and five patients, respectively. The tuberculous culture was positive in only two. The most common radiological findings were ascites (100%) and omental involvement (65.2%). A laparoscopy was performed in nine of 23 patients. A total of 22 patients completed anti-tuberculous therapy successfully and were cured, except one with cirrhosis. CONCLUSION: Tuberculous peritonitis may be fatal but is medically cured if diagnosed in a timely fashion. Although both non-invasive and invasive tests have additional benefits, clinician suspicion is still the first step for the diagnosis of tuberculous peritonitis.
Keywords: abdominal; diagnosis; extra-pulmonary; peritonitis; tuberculosis